PTH-034 The Safe And Effective Treatment Of Iron Deficiency With Iron Isomaltoside 1000 - Clinical Experience From A Uk Gastroenterology Unit. (9th June 2014) - Williams, E; Craven, L; Surgenor, S; Bapat, U; Strom, C; Snook, J
Abstract : Introduction: Parenteral iron has been used increasingly over the last decade to treat specific patient groups with iron deficiency (ID) anaemia. There is, however, limited evidence of safety and efficacy in all patients with ID, particularly those with underlying malignancy or inflammation. Methods: Data from all outpatients receiving iv iron isomaltoside (Monofer) for confirmed ID between 1st April and 31st December 2012 at our UK District General Hospital was analysed, regardless of underlying diagnosis or comorbidity. Patients received their infusions under the care of Gastroenterology on our Medical Investigations Unit, a 7-day nurse led unit that works extended hours and is located within the main hospital. ID was defined by ferritin <24 mcg/l, transferrin saturation index (TSAT) <15% or a blood film compatible with ID. Anaemia was defined as a low haemoglobin concentration (Hb) (men <130 g/l, women <115 g/l). Data was collected for each patients first treatment within the study period only, albeit 1 or 2 infusions. The dose of parenteral iron was at the discretion of the referring Consultant. All patients had post infusion bloods, 75 (88%) within 4 weeks. Data on the cause of ID and significant comorbidity was collected. Results: 85 patients received monofer infusions for confirmed ID over the study period, with 80 of these having ID anaemia. Referrals were from a range of medical, surgical and oncological specialities. 55 patients (65%) were female and the age range was 18–92 years (median 73 years). Baseline bloods (median and interquartile range (IQR)) were Hb 90 g/l (80–99), Mean Cell Volume 81 fl (72–88), Mean Cell Haemoglobin 24.8 pg (22.2–28.0), ferritin 15mcg (9–24) and TSAT 9% (5–15). Most patients had extensive comorbidity; 29(34%) had active malignancy and 44(77%) of those without malignancy had active inflammation. The median iron dose was 14.6 mg/kg (IQR 11.2–17.5). No significant adverse reactions occurred and all patients received the full infusion. Post infusion bloods demonstrated a median increase in Hb of 23 g/l (Figure 1 ) with 52% having a Hb increase of >20 g/l. The Hb rise was significantly higher in individuals with a lower baseline Hb; regression slope of baseline against change in Hb = -5.9 Hb, p < 0.0001. Conclusion: Treatment of ID anaemia with parenteral iron is safe and effective in all patients including those with cancer or active inflammation. A rapid rise in Hb within 4 weeks is seen in many patients particularly where the baseline Hb is low. Disclosure of Interest: None Declared.